Preparation, structural characterization, and electrical conductivity of highly ion-conducting glasses and glass ceramics in the system Li1+xAlxSnyGe2-(x+y)(PO4)3 - Santagneli, Silvia H. [UNESP]; Baldacim, Helio V. A. [UNESP]; Ribeiro, Sidney J. L. [UNESP]; Kundu, Swarup; Rodrigues, Ana Candida Martins; Doerenkamp, Carsten; Eckert, Hellmut (American Chemical Society (ACS), 2016)
Highly ion conducting glass-ceramics, crystallizing in the Na-superionic conducting (NASICON) structure, have been prepared in the system Li1+xAlxSnyGe2-(x+y)(PO4)3 by crystallization of glassy precursor samples. For modest substitution levels (y = 0.25), these crystalline solid solutions show slightly higher electrical conductivity than corresponding samples without Sn, supporting the rationale that the lattice expansion associated with the substitution of Ge by its larger homologue Sn can enhance ionic conductivity. Higher Sn substitution levels (y = 0.45) do not result in any improvement. The glass-to-crystal transition has been characterized in detail by multinuclear single and double resonance NMR experiments. While substantial changes in the 31P and 27Al MAS NMR spectra indicate that the crystallization of the glasses is accompanied by significant modifications in the local environments of the phosphate and the aluminum species, the dipolar solid state NMR experiments indicate that the structures of both phases are dominated by Ge-O-P, Sn-O-P, and Al-O-P connectivities. Substitution of Ge by Al and Sn in the crystalline NASICON structure results in a binomial distribution of multiple phosphate environments, which differ in the number of P-O-Ge, P-O-Al, and P-O-Sn linkages. While there is no chemical shift discrimination between P-O-Al and P-O-Sn linkages, an unambiguous distinction is possible on the basis of 31P{27Al} rotational echo adiabatic passage double resonance (REAPDOR) experiments.